The influence of intraoral devices in competitive anxiety levels of golf athletes : a pilot study - Cebola, Pedro (2019)
Poster presented at the 3rd International Congress of CiiEM - Research and Innovation in Human and Health Sciences. Campus Egas Moniz, Monte da Caparica, Portugal, 20-22 June 2018